Beryl’s Chocolate and Confectionery Sdn Bhd to Enter Malaysia Market - Suwannikda Thebpharith A/P Wan Di; Daisy Mui Hung Kee; Nurul Imaani Bt Mohd Noor Hashim; Syahirah Binti Azizan; Nur Izza Ain Binti Mohd Ezani; Nourah AlMousa (Journal of The Community Development in Asia, 2019)
Chocolate and confectionery food market is really competitive in Malaysia. This paper will elaborate ways how Beryl’s Chocolate and Confectionery Sdn Bhd to enter and introduce it product in local market. Beryl’s Chocolate is a brand name for high quality with affordable price overseas, especially Japan. But Beryl’s Chocolate is an unknown brand for local citizen.